Neuronal Correlates of Auditory Streaming in Monkey Auditory Cortex for Tone Sequences without Spectral Differences - Knyazeva, Stanislava; Selezneva, Elena; Gorkin, Alexander; Aggelopoulos, Nikolaos C.; Brosch, Michael (Frontiers in Integrative Neuroscience, 2018)
This study finds a neuronal correlate of auditory perceptual streaming in the primary auditory cortex for sequences of tone complexes that have the same amplitude spectrum but a different phase spectrum. Our finding is based on microelectrode recordings of multiunit activity from 270 cortical sites in three awake macaque monkeys. The monkeys were presented with repeated sequences of a tone triplet that consisted of an A tone, a B tone, another A tone, and then a pause. The A and B tones were composed of unresolved harmonics formed by adding the harmonics in cosine phase, in alternating phase, or in random phase. A previous psychophysical study on humans revealed that when the A and B tones are similar, humans integrate them into a single auditory stream; when the A and B tones are dissimilar, humans segregate them into separate auditory streams. We found that the similarity of neuronal rate responses to the triplets was highest when all A and B tones had cosine phase. Similarity was intermediate when the A tones had cosine phase and the B tones had alternating phase. Similarity was lowest when the A tones had cosine phase and the B tones had random phase. The present study corroborates and extends previous reports, showing similar correspondences between neuronal activity in the primary auditory cortex and auditory streaming of sound sequences. It also is consistent with Fishman's population separation model of auditory streaming.